Genomic analysis and identification of potential duplicate accessions in Burkina Faso cassava germplasm based on single nucleotide polymorphism - Soro, Monique; Pita, Justin S.; Somé, Koussao; Otron, Daniel H.; Yéo, Edwige; Mutuku, J. Musembi; Néya, James B.; Tiendrébéogo, Fidèle; Koné, Daouda (Frontiers in Sustainable Food Systems, 2023)
Genetic adaptation of cassava to the unpredictable climatic conditions and its resistance to viruses’ diseases are an essential prerequisite for reaching out food security in sub-Saharan Africa. The accessions collected in farmers' fields are very important as they can provide sources of novel genetic variability crucial for achieving this objective. In this study, a panel of 184 accessions collected in Burkina Faso was genotyped using 36 single nucleotide polymorphism (SNPs) markers. SNPs markers and accessions which had more than 6% missing data were removed from dataset and the remaining 34 markers, and 166 accessions were retained for genetic diversity and population structure assessment. The results revealed high genetic diversity indicated by the average expected heterozygosity (0.46), the observed heterozygosity (0.58), and the polymorphic information content (0.36). A complex genetic structure of 166 accessions was observed through the formation of seventeen clusters using DAPC and two clusters using Bayesian analysis. Out of the 166 accessions, 79 were unique multilocus genotypes (MLGs) and 87 were potential duplicates. For the 79 MLGs, DAPC suggested eight clusters and Bayesian analysis seven clusters. Clusters suggested by DAPC seemed to be more consistent with higher probability of assignment of the accessions within the clusters. PCoA showed the lack of clustering according to geographical origin. Information related to breeding patterns and geographic origin did not provide clear differentiation between the clusters according to the AMOVA. In contrast, the FST was maximized when considering the clusters suggested by the Bayesian and DAPC analyses. The results of this study will be useful for cassava germplasm conservation and breeding programs.